Radiation damage by extensive local water ionization from two-step electron-transfer-mediated decay of solvated ions - Gopakumar, G; Unger, I; Slavíček, P; Hergenhahn, U; Öhrwall, G; Malerz, S; Céolin, D; Trinter, F; Winter, B; Wilkinson, I; Caleman, C; Muchová, E; et al. (Nature chemistry, 2023)
Biomolecular radiation damage is largely mediated by radicals and low-energy electrons formed by water ionization rather than by direct ionization of biomolecules. It was speculated that such an extensive, localized water ionization can be caused by ultrafast processes following excitation by core-level ionization of hydrated metal ions. In this model, ions relax via a cascade of local Auger-Meitner and, importantly, non-local charge- and energy-transfer processes involving the water environment. Here, we experimentally and theoretically show that, for solvated paradigmatic intermediate-mass Al3+ ions, electronic relaxation involves two sequential solute-solvent electron transfer-mediated decay processes. The electron transfer-mediated decay steps correspond to sequential relaxation from Al5+ to Al3+ accompanied by formation of four ionized water molecules and two low-energy electrons. Such charge multiplication and the generated highly reactive species are expected to initiate cascades of radical reactions.